2020
DOI: 10.18295/squmj.2020.20.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Hidradenoma of the Breast Diagnosed on a Core Needle Biopsy: A case report and review of the literature

Abstract: Clear cell hidradenoma (CCH) is a tumour originating from the eccrine sweat glands. It usually presents in the limbs, axilla or trunk. CCH of the breast is rare and can present as a cystic lesion in the breast that can be easily misdiagnosed as malignancy. We report a 36-year-old female patient who presented at the Sultan Qaboos University Hospital Breast Clinic, Muscat, Oman, in 2018 with a lump in her left breast. Ultrasound examination reported a complex cystic lesion with a solid, vascular component. An ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…[ 8 , 9 ] Breast CCH is rare, and some studies have indicated that it may coexist with both eccrine sweat glands and mammary ducts. [ 10 ] When CCH is situated within the mammary duct, its ultrasound appearance manifests as a cystic lesion within the deep breast tissue. In such cases, the lesion is no longer confined to the skin layers, posing challenges in distinguishing it from intraductal papillomas on ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 9 ] Breast CCH is rare, and some studies have indicated that it may coexist with both eccrine sweat glands and mammary ducts. [ 10 ] When CCH is situated within the mammary duct, its ultrasound appearance manifests as a cystic lesion within the deep breast tissue. In such cases, the lesion is no longer confined to the skin layers, posing challenges in distinguishing it from intraductal papillomas on ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor is composed of polyhedral, squamoid, clear, poroid / transitional and rarely mucinous cells. 10 To diagnose malignancy, there should be infiltrative growth pattern, deep extension, nuclear pleomorphism, necrosis, vascular or perineural invasion, Mitosis of 4 or more/ 10 HPF, Ki -67 > 11%, PHH3 > 0.7% reported in malignant cases. 11 Immunohistochemistry studies are usually positive for cytokeratins, CEA, EMA, GCDFP-15 and p63, but negative for vimentin.…”
Section: Discussionmentioning
confidence: 99%